Trinuclear CuII Structural Isomers: Coordination, Magnetism, Electrochemistry and Catalytic Activity towards the Oxidation of Alkanes - Sutradhar, Manas (2018)
The reaction of the Schiff base (3,5-di-tert-butyl-2-hydroxybenzylidene)-2-hydroxybenzohydrazide (H3L) with copper(II) nitrate, acetate or metaborate has led to the isomeric complexes [Cu3(L)2(MeOH)4] (1), [Cu3(L)2(MeOH)2]·2MeOH (2) and [Cu3(L)2(MeOH)4] (3), respectively, in which the ligand L exhibits dianionic (HL2–, in 1) or trianionic (L3–, in 2 and 3) pentadentate 1κO,O′,N:2κN′,O″ chelation modes. Complexes 1–3 were characterized by elemental analysis, IR spectroscopy, single-crystal X-ray crystallography, electrochemical methods and variable-temperature magnetic susceptibility measurements, which indicated that the intratrimer antiferromagnetic coupling is strong in the three complexes and that there exists very weak ferromagnetic intermolecular interactions in 1 but weak antiferromagnetic intermolecular interactions in both 2 and 3. Electrochemical experiments showed that in complexes 1–3 the CuII ions can be reduced, in distinct steps, to CuI and Cu0. All the complexes act as efficient catalyst precursors under mild conditions for the peroxidative oxidation of cyclohexane to cyclohexyl hydroperoxide, cyclohexanol and cyclohexanone, leading to overall yields (based on the alkane) of up to 31 % (TON = 1.55 × 103) after 6 h in the presence of pyrazinecarboxylic acid.